Case Book of Brief Psychotherapy with College Students. - Whitaker, Leighton (Taylor and Francis, 2014)
Short-term therapy doesn't have to be second-best!This valuable book explores a variety of brief therapy approaches with young adults between 17 and 25. Each case discussion thoroughly covers the salient points of the client, the problem, and the treatment, as well as segments of the treatment transcripts that illustrate the critical aspects of the counseling. A post-hoc question-and-answer section explores alternative ways the therapist could have handled the client and allows in-depth examination of successful treatment approaches. Case Book of Brief Psychotherapy with Co.